2019
DOI: 10.1159/000493983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Language Background on the Development of Sociolinguistic Awareness: The Perception of Accent Variation in Monolingual and Multilingual 5- to 7-Year-Old Children

Abstract: As a result of complex international migration patterns, listeners in large urban centres such as London, UK, likely encounter large amounts of variation in spoken language. However, although dealing with variation is crucial to communication, relatively little is known about how the ability to do this develops. Still less is known about how this might be affected by language background. The current study investigates whether early experience with variation, specifically growing up bilingually in London, affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…Much less research has examined accent identification in the context of bilingual communities. Evans and Lourido (2019) replicated Wagner et al (2014)'s study with monolingual children in London, U.K., but also showed that bilingual children were able to discriminate talkers in all three conditions (native vs. regional, regional vs. L2 and native vs. L2), suggesting that early experience with variation benefits identification of talkers from different language backgrounds. Arguably, bilingual children had more exposure to variation in a community where that variation is useful in identifying talkers and navigating relationships (Evans and Lourido 2019, p. 156), and this most likely led to an earlier development of sociolinguistic awareness in comparison to monolingual peers.…”
Section: Literature Review 21 Identifying Accents and Talkerssupporting
confidence: 54%
See 1 more Smart Citation
“…Much less research has examined accent identification in the context of bilingual communities. Evans and Lourido (2019) replicated Wagner et al (2014)'s study with monolingual children in London, U.K., but also showed that bilingual children were able to discriminate talkers in all three conditions (native vs. regional, regional vs. L2 and native vs. L2), suggesting that early experience with variation benefits identification of talkers from different language backgrounds. Arguably, bilingual children had more exposure to variation in a community where that variation is useful in identifying talkers and navigating relationships (Evans and Lourido 2019, p. 156), and this most likely led to an earlier development of sociolinguistic awareness in comparison to monolingual peers.…”
Section: Literature Review 21 Identifying Accents and Talkerssupporting
confidence: 54%
“…This idea is similar to explanations of how children develop awareness of regional accent variation. Wagner et al (2014) argue that children have a gradient representation of accent variation in which the native accent forms the core set of experience and other accents are categorised in relation to that core (see also Evans and Lourido 2019). One possibility is that such gradient representations not only form the basis of adult representations, but that they continue to be used in adulthood.…”
Section: The Neofalantes' Accent As An Emerging Varietymentioning
confidence: 99%
“…Beyond specific exposure to particular varieties, overall exposure to variation may also contribute to performance in dialect perception tasks. For example, Evans et al (2016) observed higher accuracy in the regional dialect condition of their ad hoc identification task for multilingual children than for monolingual children. They interpreted this result in terms of exposure to variation: multilingual children have more exposure to language variation in their environment and may therefore exhibit better performance in tasks that require them to associate phonetic variation with social groups.…”
Section: Discussionmentioning
confidence: 98%
“…Previous work using ad hoc identification tasks suggested that 5- to 6-year-old children could not successfully identify regional varieties (Floccia et al, 2009; Girard et al, 2008; Wagner et al, 2014; cf. Evans et al, 2016). The results of the current study support those findings: children in Experiment 1 did not succeed with any contrasts until 6–7 years old, and were not consistently successful until 10–11 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation